Gain measurements on VCSEL material using segmented contact technique. (16th February 2023) - Hentschel, C; Allford, C P; Gillgrass, S-J; Travers-Nabialek, J; Forrest, R; Baker, J; Meiklejohn, J; Powell, D; Meredith, W; Haji, M; Davies, J I; Shutts, S; et al.
Abstract: We report direct measurements of the optical gain on vertical-cavity surface-emitting laser (VCSEL) material using a stripe-length method featuring segmented contacts. We utilise the similarity of the in-plane transverse electric (TE) polarised matrix element and that of the VCSEL lasing mode and a simple method to reduce round trip effects. The confinement factor is determined from cold-cavity simulations of the in-plane TE polarised slab waveguide mode and used to convert the measured in-plane modal gain into the vertical-cavity modal gain, as required for the VCSEL structure. This gives a threshold material gain of 1440 ± 140 cm −1 at 30 °C for this structure. A comparison with the threshold material gain values determined from the lasing condition, where internal optical losses due to doping induced absorption is included using parameters taken from the literature, indicates the presence of an additional source of optical loss in the experiment which increases the threshold material gain by ∼450 cm −1 . A best fit is obtained by increasing the optical loss in the n-DBR (distributed Bragg reflectors) layers to 40 cm −1, which is consistent with previous work on additional scattering losses due to interface roughening in the n-DBR layers. To further demonstrate the utility of this method for rapid optimisation, the gain-peak wavelength is measured directly, and its temperature dependence is compared to the lasing wavelength.